National Survey of Pharmacy Leadership at Ministry of Health in Saudi Arabia: Communication and Relationship Strategies - Alomi, Yousef Ahmed; Abdulmohsen Albaz, Modhi; AlMuhraj, Wejdan Fawzan; AlKharji, Mashael Yasser; Alshuraym, Norah Rushud (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the national survey of pharmacy leadership of the Ministry of Health with emphasis on pharmacy communication strategies. Methods: It is a ninety days cross-sectional national survey of pharmacy leadership practice at Ministry of Health. The survey modified from self-assessment of 360 leadership and with pharmacy leadership literature. It consisted of a demographic section, leadership pathway, and fifty-three leadership questions. It contained selected eighteen leadership skills of 360 leadership, self-assessment. Of The leadership skills included Achievement, Goals, Flexibility, Feedback, Excellence, Empowering Others, Emotional Intelligence, Decision Making, Developing Others, Cultural Awareness, Continual Improvement, Communication Skills, Coworker Development, Leading the Change Needed, Attitude, Analytical, Administrative Skill, and Action. The electronic format of the survey through the survey monkey system and distributed through emails. All analysis is done through the survey monkey system. The survey divided into several parts for analysis, and discussion. Part one: practice management, part two: planning and organizations, part three: communications and relationship strategies, part four: problem-solving and decision making, part five: performances management, part six; working environment, and part seven: professional development. The study explored the part number three; National Survey of Pharmacy leadership: communication and relationship strategies. Results: The survey distributed to one hundred hospitals, the response rate, was forty-two hospitals (42%) with seventy-pharmacy leaders. The gender distribution of responders was Male 43 (63.24%) and female 25 (36.76%) while the nationality was Saudi 69 (98.57%) and non-Saudi one (1.43%). Most responders were in the age range (25-34 years) 30 (55.12%) and (35-44 years) 26 (38.24%). The average score Communication skills were 2.62 (87.32%) with the highest score was shared valuable information with others 2.79 (92.99%) and listens to others’ points of view with an open mind was 2.79 (92.99%). The lowest score was coach others and provides feedback on the use of different oral communication styles for different audiences 2.47 (82.32 %), and checks for understanding throughout conversations or group was 2.48 (82.65 %). Conclusion: The communication strategies of pharmacy leaders are acceptable at Ministry of Health institution in Saudi Arabia. The pharmacy leaders demand special management education and training programs. The annual survey of pharmacy leadership is highly recommended at MOH organization in Kingdom of Saudi Arabia.
Keywords: Pharmacy leadership; Communication; Relationship strategies; Ministry of Health; Saudi arabia